A STUDY ON ADVANCEMENTS IN CARBON MINERALIZATION FOR PERMANENT CO₂ STORAGE TO PREVENT ENVIRONMENTAL DEGRADATION - Aadik Behl (International Educational Journal of Science and Engineering, 2025)
This study explores carbon mineralization as a promising method of permanent CO₂ storage to mitigate climate change. Carbon mineralization is the CO₂ conversion into stable carbonates by reaction with minerals like olivine, serpentine, or basalt. The geochemical processes behind this technology are researched, such that the technology has the potential to be an effective and sustainable sequester of CO₂. Drawing on the current state of the research as well as ex-situ and in-situ approaches, the study determines the industrial byproducts that can boost the implementation on a large scale. It was found that carbon mineralization technology has improved carbon sequestration efficiency significantly; yet, it is challenged by scale due to its energy requirements and mineral availability, as it requires a sufficiently developed infrastructure. Policy support and public-private collaboration are also recognized in the study to address the identified barriers. Semi-quantitative analyses such as t-tests and correlation matrices shed light on the interrelationships between the success of technologies, their economic viability, and the role of government incentives. The results are used to argue that carbon mineralization can become an essential contribution to global carbon dioxide mitigation strategies as technology advances and appropriate policy structures interweave. This work provides insight into the long-term viability of carbon mineralization to reach climate goals.